Inguinal hernia repair under crisis: a retrospective cohort study of surgical outcomes across the COVID-19 era in China - Jagdewsing, Dhierin Roman; Elijah, Wally; Mohammedzeyn, Ahmed A.; Kwakye, Omane V.; Singh, Yachin; Mahmud, N M Motachim; De Alwis, R. A. Geehari Mihinsa; Rashidi, Masoumeh; Moharam, Hania; Iqbal, Fariya (Journal of minimally invasive surgery, 2025)
The coronavirus disease 2019 (COVID-19) pandemic has affected healthcare systems worldwide, altering clinical practices and surgical outcomes. However, its specific impact on inguinal hernia repair (IHR) has not been extensively studied. This research investigates the effects of the pandemic on surgical outcomes and the evolution of surgical techniques during the COVID-19 era. The impact of the COVID-19 pandemic on surgical site infections (SSIs), secondary infections, postsurgical pain, edema, and the shift in surgical techniques in IHR patients. This study is a retrospective cohort study involving 1,067 patients who underwent elective unilateral IHR from 2018 to 2024 at the Second Affiliated Hospital of Dalian Medical University, who were categorized into three groups based on the time of surgery: pre=pandemic (n = 239), pandemic (n = 592), and post-pandemic (n = 236).Clinical variables included surgical techniques, SSI classification, postsurgical pain, edema, hospitalization duration, and comorbid conditions. Significant decrease in superficial and organ/space SSIs during the pandemic, particularly with laparoscopic surgery (odds ratio [OR], 0.13; = 0.002). Post-pandemic, there was a significant reduction in mild, moderate, and severe pain (OR, 0.085, 0.127, and 0.029; all < 0.001). Additionally, there was a marked increase in the use of laparoscopic surgery, from 9.6% pre-pandemic to 77.1% post-pandemic ( < 0.001). The post-pandemic group was associated with improved surgical outcomes, including reduced SSI rates, postsurgical pain, and shorter hospital stays, likely due to the increased use of laparoscopic surgery. These findings underscore the importance of adapting surgical approaches in response to crisis-driven changes.